ANALYSIS OF TABAROK FINANCING BASED ON MUDHARABAH AGREEMENT IN TSQ COOPERATIVE - Wahyuningsih, Sri; Matnin, Matnin; Roziy, Fathur (Ngejha, 2024)
This study aims to analyze Tabarok financing from the perspective of mudharabah financing contracts at KSPPS Tabarok Shohibul Qorib Pamekasan. This research approach is an object of field research using a qualitative approach, which is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behaviors. In this case, the researcher uses a qualitative approach because the research approach is directed to achieve the goal of obtaining an in-depth explanation of the application of a theory. So it is required to use more inductive thinking. Based on the results of research on the application of tabarok financing with the mudharabah scheme in the review of fiqh muamalah at KSPPS Tabarok Shohibul Qorib Pamekasan as follows: first, the mechanism for determining profit sharing in Tabarok financing products is based on the formula for calculating the results of observations in the field that has been determined by KSPPS TABAROK TSQ, The ratio of profit sharing of tabarok breeding is 20% for cooperatives while 80% share for customers is taken infaq shodaqoh 2.5% Profit sharing calculation system applied by KSPPS TSQ in products is using the profit principle (profit sharing calculation based on sales and/or gross income from business after deducting costs). Second, regarding the period of daily return of capital (savings), fiqh experts argue about the limitation of the period of mudharabah. Some scholars argue that the existence of time (daily) restrictions can prevent entrepreneurs from developing their businesses so maximum profits from these activities are difficult to achieve. However, other scholars argue that financiers and businessmen may have reached agreement on this.